Customer service more than a smile (Baltimore County Public Library, Townson, Md. : Library Video Network, 1991)
The purpose of this video/training package is to promote good customer service among all levels of library staff, including staff behind the scenes.
Copy also available in DVD format
Keywords: Customer services; Customer relations